#TITLE_ALTERNATIVE# - REGINA (NIM 12206021); Pembimbing: Dr. Ir. Sudjati Rachmat, DEA., ASHA
Hydraulic fracturing is one of reservoir stimulation that used for recovering well productivity. Commonly, low permeability reservoir is allowed to do hydraulic fracturing. In this paper presents about single layer hydraulic fracturing with P3D model. P3D model is fracture geometry that ilustrates fracture in three dimension where consider about fracture half length, fracture width, and fracture height. Sensitivity analysis is used in hydraulic fracturing design to know relationship between fracture geometry and variable such as injection rate and proppant concentration. In addition, economic optimization is calculated to get optimum NPV. From simulation, the optimum NPV is US$ 130.816 at design Xf = 150 ft, qi = 15 bpm, and proppant concentration 4 ppa.